Hospitalized Coronavirus Disease 2019 (Covid-19) with Pre-existing Diabetes Mellitus: Comparison between Survived and Deceased Patients - Morshed, Md Shahed; Mosabbir, Abdullah Al; Hossain, Mohammad Sorowar (Bangladesh Journal of Microbiology, 2023)
Patients with pre-existing diabetes mellitus (DM) are at high risk of severe outcomes from coronavirus disease 2019 (COVID-19). However, there is limited data on these patients from South Asia, especially Bangladesh. Besides, comparative studies between survived and deceased patients with DM and COVID-19 are rare in literature. This retrospective cross-sectional study was conducted among RT-PCR confirmed COVID-19 patients with pre-existing DM in a specialized COVID-19 hospital in Bangladesh. Data from hospital records were analyzed. Among 921 RT-PCR confirmed patients with COVID-19 admitted during the study period, 231 (~25%) patients had pre-existing DM. The overall mortality and intensive care unit (ICU) mortality rate among patients with DM was 11.3% (26/231) and 46.2% (12/26), respectively. The median age of the deceased patients was slightly higher (63.5 vs. 59 years, p 0.21). The most common comorbidity in both groups was hypertension. The clinical features were not significantly different between survived and deceased. However, deceased patients had significantly lower blood oxygen level (85% vs. 93%, p <0.001), and higher neutrophil-lymphocyte ratio (7.9 vs. 4.5, p 0.003) and serum ferritin levels (946.0 vs. 425.0 ng/mL, p 0.03). Glycemic status was poor in both groups. This study would help identify a subgroup of diabetic patients with COVID-19 who are at higher risk of in-hospital death requiring rigorous clinical management. Bangladesh J Microbiol, Volume 39, Number 1, June 2022, pp 1-6